An Empirical Multi-Sector Investigation of Corporate Governance Practices and Their Impact on the Financial Performance of Sri Lankan Listed Companies - Sivanathan, Sivaruban (2025)
This study investigated the relationship between corporate governance practices and the financial performance of multiple sectors of listed companies in Sri Lanka from 2014 to 2023. The literature review highlighted key governance issues, particularly the conflicts of interest between majority and minority shareholders. The study addressed the research gaps in terms of evidence, knowledge, population scope, and deficiencies in empirical analysis. The study focused on several governance attributes: Board Size, Board Gender Diversity, the Related Party Transactions Review Committee, Cybersecurity, and Environmental, Social, and Governance factors. These elements significantly impact corporate governance practices and, ultimately, financial performance. Key accounting ratios were employed to evaluate financial performance—Net Profit Margin, Return on Assets, Return on Equity, and Tobin’s Q—while Sales served as a control variable. A quantitative methodology was applied, utilising regression analysis and secondary data from published sources. The analysis revealed significant relationships between board size and ESG factors, as well as their impact on return on assets. Additionally, cybersecurity demonstrated a strong positive correlation with both return on assets and return on equity. Industry-level analysis revealed a consistent link between corporate governance and financial performance, except in the real estate sector. A comparative assessment of Sri Lanka’s corporate governance codes from 2013 and 2017 found that the 2013 code had a more statistically significant impact on financial performance. The findings suggest that board size, cybersecurity, and ESG practices have a positive impact on financial outcomes. In contrast, board gender diversity and the RPTRC may require greater policy focus and organisational support to yield the desired impact, particularly in emerging capital markets like Sri Lanka.